Recent Advances in Liver Resection for Hepatocellular Carcinoma - Morise, Zenichi; Kawabe, Norihiko; Tomishige, Hirokazu; Nagata, Hidetoshi; Kawase, Jin; Arakawa, Satoshi; Yoshida, Rie; Isetani, Masashi (Frontiers in Surgery, 2014)
Hepatocellular carcinoma (HCC) is the most common primary liver malignancy. The association of HCC with chronic liver disease is well known and making treatment complex and challenging. The treatment of HCC must take into consideration, the severity of chronic liver disease, the stage of HCC, and the clinical condition of the patient. Liver resection (LR) is one of the most efficient treatments for patients with HCC. Better liver function assessment, increased understanding of segmental liver anatomy using more accurate imaging studies, and surgical technical progress are the important factors that have led to reduced mortality, with an expected 5 year survival of 38-61% depending on the stage of the disease. However, the procedure is applicable to less than 30% of all HCC patients and 80% of the patients after LR recurred within 5 years. There are recent advances and prospects in LR for HCC in several aspects. 3-dimensional computed tomography imaging assisted preoperative surgical planning facilitates unconventional types of LR. Emerging evidences of laparoscopic hepatectomy and prospects for the use of newly-developing chemotherapies as a combined therapy may lead to expanding indication of LR. LR and liver transplantation could be associated rather than considered separately with the current concepts of “bridging LR” and “salvage transplantation”.